Communication of medical errors in a simulated clinical scenario. Experience with a pediatric residency group - María Pico; Ximena Prado; Gonzalo Germán Guiñazú; Sofía Diana Menéndez; Julia Dvorkin; María Victoria López; Carolina Pascual; Christian Elias Costa; Diego Enríquez (Sociedade de Pediatria de São Paulo, 2023)
ABSTRACT Objective: To determine the performance of groups of pediatric residents from a Buenos Aires hospital, in terms of correct recognition and communication of a medical error (ME), in a high-fidelity simulation scenario. To describe the reactions and communication attempts following the ME and the self-perception by the trainees before and after a debriefing. Methods: Quasi-experimental uncontrolled study conducted in a simulation center. First- and third-year pediatric residents participated. We designed a simulation case in which an ME occurred and the patient deteriorated. During the simulation, participants had to provide information on communicating the ME to the patient's father. We assessed communication performance and, additionally, participants completed a self-perception survey about ME management before and after a debriefing. Results: Eleven groups of residents participated. Ten (90.9%) identified the ME correctly, but only 27.3% (n=3) of them reported that a ME had occurred. None of the groups told the father they were going to give him important news concerning his son's health. All 18 residents who actively participated in this communication completed the self-perception survey, with an average score before and after debriefing of 5.00 and 5.05 (out of 10) (p=0.88). Conclusions: We observed a high number of groups that recognized the presence of a ME, but the communication action was substantially low. Communication skills were insufficient and residents' self-perception of error management was regular and not modified by the debriefing.